PENGARUH PENGETAHUAN AWAL DAN TES FORMATIF TERTULIS BERBASIS WEBSITE TERHADAP HASIL BELAJAR FISIKA SISWA MTs NEGERI BATAM - JURAHMIN JURAHMIN (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2021)
This study aims to determine: (1) Differences in physics learning outcomes between students who are given a website-based formative written test and students who are given a paper and pencil-based formative written test; (2) The effect of the interaction between a website-based formative written test and a written formative test based on a website, paper and pencil, and the level of initial knowledge of physics learning outcomes; (3) The difference in physics learning outcomes between students who were given a website-based formative written test and a paper and pencil-based formative written test in a group of students who had a high level of initial knowledge; and (4 ) Differences in physics learning outcomes between students who were given a website-based formative written test and a paper and pencil-based written formative test in a group of students who had a low level of initial knowledge. This research uses experimental method with treatment by level fixed model design. The population of the entire class VIII of MTsN Batam for the academic year 2010/2011 is 10 classes. The research sample was determined by multi-stage random sampling consisting of 4 classes. Two experimental classes 1 were given a website-based formative written test and two experimental classes 2 were given a paper and pencil-based written formative test. Each treatment consisted of 40 students. The technique of collecting initial knowledge data and learning outcomes data is done by testing. Test requirements analysis was carried out with normality test and homogeneity test. The research hypothesis was tested using two-way ANOVA and further tests were carried out with the Tukey test. Based on the results of data analysis, it can be concluded: (1) Overall, the learning outcomes of students who are given a written formative test based on a website are higher than students who are given a written formative test based on paper and pencil; (2) There is an interaction effect between written formative tests and the level of initial knowledge. on physics learning outcomes; (3) Overall, in the group of students who have a high level of initial knowledge, the learning outcomes of students who are given a website-based formative written test are higher than students who are given a paper and pencil-based written formative test; and (4) Generally Overall, in the group of students who have a low level of prior knowledge, the learning outcomes of students who are given a paper and pencil-based formative written test are higher than students who are given a website-based formative written test. ABSTRAKPenelitian ini bertujuan untuk mengetahui: (1) Perbedaan hasil belajar fisika antara siswa yang diberikan tes formatif tertulis berbasis website dengan siswa yang diberikan tes formatif tertulis berbasis paper and pencil; (2) Pengaruh interaksi antara tes formatif tertulis berbasis website, tes formatif tertulis berbasis paper and pencil, dan tingkat pengetahuan awal terhadap hasil belajar fisika; (3) Perbedaan hasil belajar fisika antara siswa yang diberikan tes formatif tertulis berbasis website dan tes formatif tertulis berbasis paper and pencil pada kelompok siswa yang memiliki tingkat pengetahuan awal tinggi; dan (4) Perbedaan hasil belajar fisika antara siswa yang diberikan tes formatif tertulis berbasis website dan tes formatif tertulis berbasis paper and pencil pada kelompok siswa yang memiliki tingkat pengetahuan awal rendah. Penelitian ini menggunakan metode eksperimen dengan desain treatment by level fixed model. Populasi seluruh kelas VIII MTsN Batam tahun pelajaran 2010/2011 sebanyak 10 kelas. Sampel penelitian ditentukan secara multi stage random sampling terdiri 4 kelas. Dua kelas eksperimen 1 diberi perlakuan tes formatif tertulis berbasis website dan dua kelas eksperimen 2 diberikan perlakuan tes formatif tertulis berbasis paper and pencil. Masing masing perlakuan terdiri dari 40 siswa. Teknik pengumpulan data pengetahuan awal dan data hasil belajar dilakukan dengan tes. Uji persyaratan analisis dilakukan dengan uji normalitas dan uji homogenitas. Uji hipotesis penelitian menggunakan anava dua jalan dan dilakukan uji lanjut dengan uji Tukey. Berdasarkan hasil analisa data disimpulkan: (1) Secara keseluruhan, hasil belajar siswa yang diberikan tes formatif tertulis berbasis website lebih tinggi dibanding siswa yang diberikan tes formatif tertulis berbasis paper and pencil; (2) Terdapat pengaruh interaksi antara tes formatif tertulis dan tingkat pengetahuan awal terhadap hasil belajar fisika; (3) Secara keseluruhan, pada kelompok siswa yang memiliki tingkat pengetahuan awal tinggi, hasil belajar siswa yang diberikan tes formatif tertulis berbasis website lebih tinggi dari siswa yang diberikan tes formatif tertulis berbasis paper and pencil; dan (4) Secara keseluruhan, pada kelompok siswa yang memiliki tingkat pengetahuan awal rendah, hasil belajar siswa yang diberikan tes formatif tertulis berbasis paper and pencil lebih tinggi dari siswa yang diberikan tes formatif tertulis berbasis website.